Exploring new factors and the question of 'which' in user acceptance studies of healthcare software - KS Mohamadali, Noor Azizah (2013)
The importance of user acceptance of technology is critical for the success of technology implementation in the health-care sector. Spending on the procurement of new technology is growing in the hope of improving patient care as well as providing better services to the public, thus it is important that the technology is used to achieve its intended purpose. Success or failure of technology implementation depends upon the acceptance of the user and this is evident through the growing number of studies on evaluation particularly on user acceptance of the technology. While various models and frameworks have been developed to address factors associated with technology acceptance, they provide little understanding on the reasons for discrepancies in acceptance of the same system among different users. In response to this issue, this thesis proposes a theoretical model which suggests the role of ‘fit’ between user, technology and organization as an antecedent of user acceptance factors. This model was suggested based on a review of the literature and was empirically investigated on medical students’ intention to use medically related software. The proposed model in this thesis integrates three very well known existing models namely the Unified Theory of Acceptance and Use of Technology (UTAUT), the DeLone McLean IS Success Model and the Task-Technology Fit Model. The model is examined as a single model, which investigates (1) the effect of perceived fit between user, technology and organization on factors defined by UTAUT and the IS Success Model; (2) the effect of perceived fit between user, technology and organization on management support and information security expectancy construct; and (3) the effect of management support and information security expectancy on intention to use. In particular, this thesis seeks to investigate the role of ‘fit’ between user, technology and organization variable as an antecedent of performance expectancy, effort expectancy, social influence, facilitating conditions, software quality, service quality, information quality, management support and information security expectancy. This thesis also investigates the role of management support and information security expectancy constructs on intention to use which, to the best of researcher’s knowledge, have not been investigated together with an integrated model, as proposed in this thesis. Further, it presents and discusses empirical findings from the Internet survey and Drop-off approaches of 113 respondents which examined students’ intention to use medically related software using the Partial Least Square (PLS) approach to Structural Equation Modeling (SEM). WarpPLS version 3.0 software was used to analyze the empirical data in this thesis. The findings of this thesis support the hypothesized relationship proposed in the theoretical model. Specifically, the results revealed that perceived user-technology-organization fit has a significant effect on all the factors defined in the model except for social influence. The results also provide strong evidence of the relationships between the management support and information security expectancy constructs with the intention to use construct. This thesis contributes to theoretical and practical knowledge by providing, for the first time, evidence about the relationship between perceived user-technology-organization fit with constructs defined by both UTAUT and the IS Success Model. Further, the relationships between perceived user-technology-organization fit with management support and information security constructs are shown. Additionally this thesis provides empirical support on the relationship between the management support and information security expectancy constructs with the intention to use construct. The introduction and inclusion of organization fit with user and technology fit contributes to the body of knowledge in evaluation studies and provides a more complete model within user acceptance studies to help to understand the reasons for different acceptance among users of the same system or technology. Further, this thesis investigates the applicability of the multi-criteria decision analysis (MCDA) techniques to answer the question of ‘which’ in evaluation studies particularly within user acceptance studies. Existing evaluation studies provide the means to answer the question of what, why, who, when and how, but not explicitly the question of ‘which’. The question of ‘which’ needs to be explicitly addressed and specifically recognized in user acceptance studies. Although various studies implicitly provide the answer to the question of ‘which’, the importance of ‘which’ as the most critical factor or the most influential factor should be addressed explicitly in user acceptance studies. This thesis examined three well used methods which are classical AHP, Fuzzy AHP Changs’ method and Fuzzy AHP a and l method, to assign weights between various factors and subfactors of user acceptance. Acceptance factors of two different types of software were computed using each of these methods. The empirical data were collected from medical students for medically-related software and from research students for research-related software. The approaches examined, in this second part of thesis, are not intended to show which is the best method or techniques to evaluate user acceptance, but rather to illustrate the various options which are available within MCDA approaches to derive weights among evaluation items and subsequently provide an answer to address the question of ‘which’ explicitly within user acceptance studies. The results of assigning weights to factors and sub-factors using three different methods provide strong justification on the applicability of the MCDA methods as a decision support tool. The results show that these methods produced the same ranking of the factors which influence user acceptance (with slight variation using Fuzzy Chang’s method on medical software acceptance). The inclusion of the ‘which’ question can enhance evaluation studies in the health informatics research and findings related to user acceptance of health-care technology.